STRENGTHENING THE IMPACT OF ESG ON FIRM VALUE THROUGH CORPORATE GOVERNANCE: EMPIRICAL EVIDENCE FROM INDONESIA - Utami, Khalida; Indriati, Petiana; Bahri, Syamsul; Santio, Cantika Putri Permatasari (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on firm value, with corporate governance (CG) serving as a moderating variable, using data from companies listed on the Indonesia Stock Exchange. The research is motivated by the increasing emphasis on sustainability and governance practices as key drivers of long-term corporate value. Data were obtained from annual and sustainability reports over the observation period and analyzed using panel regression with a fixed-effect model. ESG disclosure was measured based on the extent of reporting across environmental, social, and governance dimensions, while CG was assessed through a composite index comprising the proportion of independent commissioners, audit committee existence, institutional ownership, and board size. The findings reveal that ESG disclosure has a negative and significant effect on firm value, proxied by Tobin’s Q, suggesting that the Indonesian capital market has not yet fully recognized ESG practices as value-enhancing factors. However, the interaction term between ESG and corporate governance (ESG×CG) exhibits a positive and significant coefficient, indicating that effective governance strengthens the impact of ESG on firm value. Additional analysis using an alternative measure of firm value (Price to Book Value or PBV) and robustness checks confirms the consistency of these results. Overall, the findings emphasize that ESG practices generate economic value only when reinforced by credible and well-functioning corporate governance mechanisms.